High-density sulfide solid electrolyte as well as pressure-maintaining sintering method and application thereof
By adopting the chemical formula of high-density sulfide solid electrolyte and the sealed pressure-holding sintering method, the existing sulfide solid electrolyte crystallinity and insufficient ionic conductivity are solved, and the electrochemical performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411636576.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
The crystallinity and ionic conductivity of existing sulfide solid electrolytes lead to poor electrochemical performance of the battery.
The chemical formula of the high-density sulfide solid electrolyte is Li7P3-x-y-2zS11-0.5x-0.5y-2zZrxSnyIn2z, and the crystallinity and ionic conductivity of the electrolyte are improved by modifying doping elements and sealed pressure-keeping sintering method.
The ionic conductivity of the sulfide solid electrolyte and the electrochemical performance of the battery are significantly improved, including the first-round charge and discharge efficiency and cycle capacity retention rate.
Smart Images

Figure CN119518076A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and more specifically, relates to a high-density sulfide solid electrolyte, a pressure-maintaining sintering method and an application thereof. Background Art
[0002] With the rapid development of energy, lithium-ion batteries have been widely used due to their excellent electrochemical properties, such as new energy electric vehicles, aerospace fields, and energy storage fields. At the same time, they are also widely used in daily life, such as button batteries for mechanical electronic watches, electric motorcycles, electric bicycles, etc. It can be said that among all batteries, lithium batteries are the most widely used, and sulfide all-solid-state lithium-ion batteries have the advantages of high energy, fast charging and discharging, good low-temperature performance, high safety, and long life, which effectively solves the series of problems of liquid lithium batteries such as low energy density, flammability, and explosion. Sulfide solid electrolytes have many advantages, which enable sulfide all-solid-state lithium batteries to have both high energy density and high rate performance. Therefore, many car companies around the world have invested in the research and development of sulfide all-solid-state lithium batteries and released mass production plans.
[0003] The key core material of sulfide all-solid-state lithium-ion batteries is sulfide electrolyte. The room temperature ionic conductivity of sulfide electrolytes reported so far has been greatly improved, but problems such as water and oxygen isolation and material crystallinity during the synthesis process still plague many researchers. For example, Yu et al. proposed an Al and O dual-doping strategy to regulate Li 3 PS 4 The chemical / electrochemical stability of the optimized Li 3.08 Al 0.04 P 0.96 S 3.92 O 0.08 The ionic conductivity of the glass ceramics is as high as 3.27 mS / cm, which is 6.8 times higher than that before doping modification. In addition, Uchida et al. focused on the process of ball milling and sintering during the synthesis of sulfides and proposed a strategy to enhance the macroscopic conductivity of glass ceramics based on changing the glass structure. 7 P 3 S 11 The ionic conductivity is 1.8 mS / cm. After secondary ball milling and powder sintering, Li 7 P 3 S 11 The ionic conductivity is 3.1mS / cm. However, the sintering of sulfide solid electrolytes reported in these studies is usually carried out in an inert atmosphere, and their crystallinity, ionic conductivity, etc. can be further improved. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high-density sulfide solid electrolyte, a pressure-maintaining sintering method and application thereof, and to solve the technical problems of the prior art solid sulfide electrolyte in terms of poor crystallinity, ionic conductivity and corresponding battery electrochemical performance by improving the electrolyte composition and sintering method.
[0005] To achieve the above object, the present invention provides a high-density sulfide solid electrolyte, the chemical formula of which is Li 7 P 3-x-y-2z S 11-0.5x-0.5y-2z Zr x Sn y In 2z , where the value ranges of x, y and z are independently 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, and x, y and z are not 0 at the same time.
[0006] Preferably, in the solid electrolyte, the value ranges of x, y and z are independently 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.2, and x, y and z are not 0 at the same time.
[0007] Further preferably, in the solid electrolyte, the value ranges of x and y are independently 0≤x≤0.2, 0≤y≤0.2, the value range of z is 0≤z≤0.1, and x, y and z are not 0 at the same time.
[0008] According to another aspect of the present invention, there is provided a method for preparing the solid electrolyte, comprising the following steps:
[0009] (1) The raw materials LiS, P 2 O 5 The modified sulfide dopant is weighed and mixed with the modified sulfide dopant according to the chemical formula element ratio of the solid electrolyte, and the mixture is pre-mixed by ball milling to obtain a uniform electrolyte precursor; wherein the modified sulfide dopant is a sulfide of one or more elements selected from Zr, Sn and In;
[0010] (2) sintering the electrolyte precursor under pressure in an inert atmosphere to obtain a flaky sulfide solid electrolyte;
[0011] (3) Grinding the flaky sulfide solid electrolyte to obtain a powdered sulfide solid electrolyte.
[0012] Preferably, in the ball-milling premixing in step (1), the mass ratio of the ball-milling raw materials to the ball-milling beads is 1:10 to 1:30, the ball-milling speed is 200 to 600 rpm, and the ball-milling time is 24 to 72 h.
[0013] Preferably, the pressure of the pressure-maintaining sintering in step (2) is maintained at 50-500 MPa, more preferably 300-400 MPa.
[0014] Preferably, step (2) is specifically as follows: placing the electrolyte precursor in a pressure-maintaining sintering mold, placing the mold under a tablet press for tableting, maintaining the pressure using a pressure-stabilizing component on the sintering mold after reaching a target pressure, and then placing the pressure-maintaining sintering mold in a heating furnace, and performing pressure-maintaining sintering in an inert atmosphere to obtain the flaky sulfide solid electrolyte.
[0015] Preferably, the electrolyte precursor is placed in a pressure-maintaining sintering mold, and then the pressure-maintaining sintering mold is placed in a tablet press. After setting a suitable pressure, the pressure-stabilizing nut is tightened, and the above steps are repeated three times to ensure that the required pressure is reached, and then the mold is placed in a tubular furnace under an inert atmosphere for pressure-maintaining sintering.
[0016] Further preferably, the pressure-maintaining sintering mold includes an upper mold and a lower mold, and ceramic gaskets are provided at the bottom of the upper mold and the top of the lower mold. When in use, the electrolyte precursor is placed between the upper mold and the lower mold; it is used to avoid direct contact between the electrolyte precursor and the stainless steel mold; sealing ceramic rings are provided on the periphery of the upper mold and the lower mold to isolate the electrolyte precursor from the outside world; a pressure divider base is provided at the lower part of the lower mold; an upper top cover is provided on the top of the upper mold, and a lower bottom cover is provided on the bottom of the lower mold, and the upper top cover and the lower bottom cover fix the upper mold and the lower mold through a fastening device.
[0017] More preferably, the fastening device comprises a fastening bolt and a fastening nut matching with the fastening bolt.
[0018] Preferably, the sintering temperature of the pressure-maintaining sintering is 200-550° C., more preferably 200-400° C., and the heating rate is 3-8° C. / min.
[0019] According to another aspect of the present invention, there is provided a use of the sulfide solid electrolyte as a solid electrolyte for a lithium ion battery.
[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0021] (1) A high-density sulfide solid electrolyte Li 7 P 3-x-y-2z S 11-0.5x-0.5y- 2z Zr x Sn y In 2zThe preferred embodiment optimizes the modified doping elements to achieve a conductivity of up to 8.82 mS / cm. After the battery is assembled, the charge and discharge rates are 0.1C. The first cycle charge and discharge specific capacities measured at room temperature are 126.62 and 119.89 mAh / g, respectively. The first cycle efficiency is 94.68%, and the capacity retention rate after 100 cycles is 91.46%, which is significantly better than the sulfide solid electrolyte in the prior art.
[0022] (2) The present invention prepares a high-density sulfide solid electrolyte by adopting a closed pressure-maintaining sintering method. The preparation method can not only effectively isolate water and oxygen, but also make the raw materials fully contact each other. Compared with the traditional sealed crucible sintering method or the sealed crucible sintering method after tableting, it also greatly improves the crystallinity of the sulfide solid electrolyte, thereby improving the ionic conductivity and the electrochemical performance of the battery when used as a lithium-ion battery electrolyte. This pressure-maintaining sintering method can be applied to the synthesis of a series of sulfide solid electrolytes, and has strong universality and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of a pressure-maintained sintering mold device used in preparing a high-density sulfide solid electrolyte by pressure-maintained sintering in some embodiments of the present invention.
[0024] Figure 2 Schematic diagram of ion transport channels of sulfide solid electrolytes prepared according to some embodiments of the present invention.
[0025] Figure 3 Impedance spectra of sulfide solid electrolytes prepared in some embodiments and comparative examples of the present invention.
[0026] Figure 4 The electrochemical performance diagrams of sulfide solid electrolytes prepared in some embodiments and comparative examples of the present invention are shown.
[0027] In all the drawings, the same figure numbers are used to represent the same elements or structures, among which: 1-upper mold; 2-lower mold; 3-ceramic gasket; 4-sealing ceramic ring; 5-pressure divider base; 6-upper top cover; 7-lower bottom cover; 8-fastening bolts; 9-fastening nuts; 10-electrolyte precursor. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0029] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0030] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0031] In the present invention, unless otherwise specified and / or described, all numerical values involving the amounts of components are "parts by weight" from beginning to end. The process parameters in the following examples without specifying specific conditions are usually based on conventional conditions.
[0032] In view of the problems of poor crystallinity and ionic conductivity of the existing sulfide solid electrolyte, the present invention provides a high-density sulfide solid electrolyte, whose chemical formula is Li 7 P 3-x-y-2z S 11-0.5x-0.5y-2z Zr x Sn y In 2z , where the values of x, y and z are independently 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, and x, y and z are not 0 at the same time.
[0033] In a preferred embodiment, the values of x, y and z are independently 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.2, and x, y and z are not 0 at the same time.
[0034] The present invention provides a method for preparing the solid electrolyte, comprising the following steps:
[0035] (1) The raw materials LiS, P 2 O 5 The modified sulfide dopant is weighed and mixed with the modified sulfide dopant according to the chemical formula element ratio of the solid electrolyte, and the mixture is pre-mixed by ball milling to obtain an electrolyte precursor; wherein the modified sulfide dopant is a sulfide of one or more elements selected from Zr, Sn and In;
[0036] (2) sintering the electrolyte precursor under pressure in an inert atmosphere to obtain a flaky sulfide solid electrolyte;
[0037] (3) Grinding the flaky sulfide solid electrolyte to obtain a powdered sulfide solid electrolyte.
[0038] In some embodiments, in the ball-milling premixing in step (1), the mass ratio of the ball-milling raw materials to the ball-milling beads is 1:10 to 1:30, the ball-milling speed is 200 to 600 rpm, and the ball-milling time is 24 to 72 h.
[0039] In some embodiments, the pressure of the pressure-maintaining sintering in step (2) is maintained at 50-500 MPa, preferably 300-400 MPa.
[0040] In some embodiments, step (2) specifically includes: placing the electrolyte precursor in a pressure-maintaining sintering mold, placing the mold under a tablet press for tableting, and maintaining the pressure using a pressure-stabilizing component on the sintering mold after reaching a target pressure, and then placing the pressure-maintaining sintering mold in a heating furnace, and performing pressure-maintaining sintering in an inert atmosphere to obtain the flaky sulfide solid electrolyte.
[0041] The pressure-maintained sintering method of the present invention can place the sulfide solid electrolyte precursor in any device that can be sintered under pressure-maintained conditions. In some embodiments, the pressure-maintained sintering mold includes an upper mold and a lower mold. When in use, the electrolyte precursor is placed between the upper mold and the lower mold; the bottom of the upper mold and the top of the lower mold are both provided with ceramic gaskets to prevent the electrolyte precursor from directly contacting the stainless steel mold; the periphery of the upper mold and the lower mold is provided with sealing ceramic rings to isolate the electrolyte precursor from the outside world; the lower part of the lower mold is provided with a pressure-dividing base; the top of the upper mold is provided with an upper top cover, and the bottom of the lower mold is provided with a lower bottom cover, and the upper top cover and the lower top cover fix the upper mold and the lower mold through a fastening device.
[0042] In some embodiments, the fastening device comprises a fastening bolt and a fastening nut matched with the fastening bolt. The sintering temperature of the pressure-maintaining sintering is 200-550° C., and the heating rate is 3-8° C. / min.
[0043] The sulfide solid electrolyte prepared by the pressure-maintaining sintering method of the present invention can be used as a solid electrolyte for lithium-ion batteries.
[0044] The following are examples and comparative examples:
[0045] Example 1
[0046] A method for preparing a high-density sulfide electrolyte material comprises the following steps:
[0047] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant ZrS 2The Li:P:S:Zr elements were mixed at a molar ratio of 7:2.9:10.95:0.1, and the mixed powder was placed in a zirconia ball mill (volume 75 ml), with a weight ratio of zirconia balls to mixed powder materials of 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0048] (2) The weighed mixed powder material and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the mixture was placed in a planetary ball mill and ball milled at a rotation speed of 510 rpm for 60 hours.
[0049] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 260 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.9 S 10.95 Zr 0.1 .
[0050] Among them, the schematic diagram of the pressure-maintaining sintering mold structure is as follows Figure 1 As shown, it includes an upper mold 1 and a lower mold 2, which are made of stainless steel. The bottom of the upper mold and the top of the lower mold are both provided with ceramic gaskets 3 to prevent the electrolyte precursor from directly contacting the stainless steel mold; the upper mold and the lower mold are provided with sealing ceramic rings 4 on the periphery to isolate the electrolyte precursor 10 from the outside world; the lower mold is provided with a pressure dividing base 5; the top of the upper mold is provided with an upper cover 6, and the bottom of the lower mold is provided with a lower bottom cover 7. The upper and lower molds are fixed by the upper cover 6 and the lower bottom cover 7 through a fastening device. The fastening device includes a fastening bolt 8 and a fastening nut 9 matched with the fastening bolt 8.
[0051] The sulfide ZrS in Example 1 2 The doping amount of is adjusted from 0.1 to 0, 0.05, 0.15 and 0.2, namely, Example 2, Example 3, Example 4 and Example 5. Other conditions are the same as Example 1, and Li 7 P 3 S 11 , Li 7 P 2.95 S 10.975 Zr 0.05 , Li 7 P 2.85 S 10.925 Zr 0.15 , Li 7 P 2.8 S 10.9Zr 0.2 Sulfide solid electrolyte.
[0052] Example 6
[0053] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant SnS 2 The Li:P:S:Sn elements were mixed in a molar ratio of 7:2.9:10.95:0.1 and the powder was placed in a zirconia ball mill (75 ml capacity) with a weight ratio of zirconia balls to the material of 20:1 (the weight ratio of a small ball with a diameter of 4 mm to a large ball with a diameter of 8 mm was 1:1).
[0054] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0055] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 260 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.9 S 10.95 Sn 0.1 .
[0056] Similarly, changing the sulfide SnS in Example 6 2 The doping amount of is adjusted to 0.05, 0.15 and 0.2, which are Example 7, Example 8 and Example 9. Other conditions are the same as Example 6, and Li 7 P 2.95 S 10.975 Sn 0.05 , Li 7 P 2.85 S 10.925 Sn 0.15 , Li 7 P 2.8 S 10.9 Sn 0.2 Sulfide solid electrolyte.
[0057] Example 10
[0058] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant In 2 S3 The Li:P:S:In element molar ratio was 7:2.8:10.8:0.2, and the powder was placed in a zirconia ball mill (volume 75 ml), with a weight ratio of zirconia balls to materials of 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0059] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0060] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 260 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.8 S 10.8 In 0.2 .
[0061] As described above, only the sulfide In in Example 10 is changed. 2 S 3 The doping amount of is adjusted to 0.05, 0.1 and 0.15 respectively, which are Example 11, Example 12 and Example 13. The other conditions are the same as Example 10, and the sulfide solid electrolyte Li can be prepared. 7 P 2.95 S 10.95 In 0.05 , Li 7 P 2.9 S 10.9 In 0.1 , Li 7 P 2.85 S 10.85 In 0.15 .
[0062] Embodiment 14
[0063] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant ZrS 2 、SnS 2The Li:P:S:Zr:Sn were mixed in an elemental molar ratio of 7:2.8:10.9:0.1:0.1, and the powder was placed in a zirconia ball mill (75 ml volume) with a weight ratio of zirconia balls to the material of 20:1 (the weight ratio of a small ball with a diameter of 4 mm to a large ball with a diameter of 8 mm was 1:1).
[0064] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0065] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.8 S 10.9 Zr 0.1 Sn 0.1 .
[0066] Embodiment 15
[0067] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant ZrS 2 、In 2 S 3 The Li:P:S:Zr:In element molar ratio was 7:2.7:10.75:0.1:0.2, and the powder was placed in a zirconia ball mill (volume 75 ml), with a weight ratio of zirconia balls to materials of 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0068] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0069] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.7 S10.75 Zr 0.1 In 0.2 .
[0070] Example 16
[0071] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant SnS 2 、In 2 S 3 The Li:P:S:Sn:In element molar ratio was 7:2.7:10.75:0.1:0.2, and the powder was placed in a zirconia ball mill (volume 75 ml), with a weight ratio of zirconia balls to materials of 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0072] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0073] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.7 S 10.75 Sn 0.1 In 0.2 .
[0074] Embodiment 17
[0075] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant ZrS 2 、SnS 2 、In 2 S 3 The elements of Li:P:S:Zr:Sn:In were mixed in a molar ratio of 7:2.6:10.7:0.1:0.1:0.2, and the powder was placed in a zirconia ball mill (volume 75 ml) with a weight ratio of zirconia balls to materials of 20:1 (the weight ratio of a small ball with a diameter of 4 mm to a large ball with a diameter of 8 mm was 1:1).
[0076] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0077] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.6 S 10.7 Zr 0.1 Sn 0.1 In 0.2 .
[0078] Comparative Example 1
[0079] (1) The raw material Li 2 S.P. 2 S 5 and sulfide dopant ZrS 2 The Li:P:S:Zr elemental molar ratio was 7:2.9:10.95:0.1, and the powder was placed in a zirconia ball mill (volume 75 ml), with a weight ratio of zirconia balls to materials of 20:1 (the weight ratio of a small ball with a diameter of 4 mm to a large ball with a diameter of 8 mm was 1:1).
[0080] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0081] (3) The precursor powder obtained after ball milling was placed in a sealed crucible and then placed in a tube furnace. The heating rate was controlled at 5°C / min. After heat treatment at 260°C in an argon environment for 3 hours, the sintered sample was placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte Li with uniform particle size. 7 P 2.9 S 10.95 Zr 0.1 .
[0082] In order to further compare and illustrate the effects of pressure-maintaining sintering, sealed crucible sintering, and tablet-pressed sealed crucible sintering on the ionic conductivity and electrochemical properties of sulfide solid electrolytes, the sintering methods described in step (3) of Example 1 to Example 17 are respectively changed to sealed crucible sintering, namely Comparative Examples 1 to Comparative Examples 17; at the same time, the sintering methods described in step (3) of Example 1 to Example 17 are respectively changed to tablet-pressed sealed crucible sintering, namely Comparative Examples 18 to Comparative Examples 34. The tablet-pressed sealed crucible sintering specifically comprises: the precursor powder obtained by ball milling is pressed into tablets under a pressure of 374 MPa, taken out and sealed in a crucible, and sintered under the same sintering temperature, heating rate, atmosphere and sintering time as the pressure-maintaining sintering to obtain a solid electrolyte.
[0083] After investigating the sulfide modifier X m S n Based on the influence of oxide X on the performance of sulfide solid electrolyte, we also studied m O n The influence of dopants is explained one by one as comparative examples.
[0084] Comparative Example 35
[0085] (1) Li 2 S:P 2 S 5 :Bi 2 O 3 =3:1:0.2 stoichiometric ratio, the powder was placed in a ball mill filled with argon (volume 75 ml), the weight ratio of zirconia balls to material was 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0086] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0087] (3) The ball-milled material is pressed into a pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened, and the above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, the heating rate is 5 ° C / min, and heat treated at 550 ° C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200 mesh sieve to obtain a sulfide solid electrolyte with uniform particle size.
[0088] Comparative Example 36
[0089] (1) Li 2 S:P 2 S 5 :GeO 2=3:1:0.1 stoichiometric ratio, the powder was placed in a ball mill filled with argon (volume 75 ml), the weight ratio of zirconia balls to material was 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0090] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0091] (3) The ball-milled material is pressed into a special pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte with uniform particle size.
[0092] Comparative Example 37
[0093] (1) Li 2 S:P 2 S 5 :SnO 2 =7:3:0.1 stoichiometric ratio, the powder was placed in a ball mill jar (75 ml) filled with argon, the weight ratio of zirconia balls to material was 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0094] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0095] (3) The ball-milled material is pressed into a special pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte with uniform particle size.
[0096] Comparative Example 38
[0097] (1) Li 2 S:P 2 S 5 :Sb 2 O 3=7:3:0.2 stoichiometric ratio, the powder was placed in a ball mill jar (volume 75 ml) filled with argon, the weight ratio of zirconia balls to material was 20:1 (the weight ratio of small balls with a diameter of 4 mm to large balls with a diameter of 8 mm was 1:1).
[0098] (2) The weighed materials and zirconia balls were sealed in a ball milling jar in a glove box filled with argon gas, and the jar was placed in a planetary ball mill and ball milled at a speed of 510 rpm for 60 hours.
[0099] (3) The ball-milled material is pressed into a special pressure-maintaining sintering mold, the pressure is set to 374 MPa and the pressure-stabilizing nut is tightened. The above steps are repeated three times to ensure that the required pressure is reached. It is then placed in a quartz tube, heated at a rate of 5 °C / min, and heat treated at 550 °C in an argon environment for 2 hours. The sintered sample is placed in a mortar and ground for 60 minutes, and sieved with a 200-mesh sieve to obtain a sulfide solid electrolyte with uniform particle size.
[0100] The composition and ionic conductivity of the sulfide solid electrolytes in each embodiment and comparative example prepared by different sintering methods are listed in Table 1 and Table 2. It should be noted that the test environment for all ionic conductivities of the present invention is room temperature. Analyzing the data in Table 1 and Table 2, the sulfide solid electrolyte after closed pressure sintering has a higher ionic conductivity. Comparing Example 17 doped with three sulfides with Comparative Example 17 and Comparative Example 34, the ionic conductivity of the former is 3.16 and 2.53 times that of the latter two. It can be seen that closed pressure sintering is better than sealed crucible sintering and tablet sealed crucible sintering. At the same time, it can also be seen from the table that the ionic conductivity of the high-entropy high-density sulfide solid electrolyte co-doped with three sulfide modifiers is significantly higher than that of single doping and double doping. Therefore, it can be said that the method for preparing high-entropy and high-density sulfide solid electrolytes provided by the present invention can not only effectively isolate water and oxygen, but also enable sufficient contact between the raw materials; at the same time, it also improves the crystallinity of the sulfide solid electrolyte, thereby improving the ionic conductivity, thereby achieving high capacity, fast charging and discharging, and long cycle performance of lithium-ion batteries.
[0101] Table 1 Composition and ionic conductivity of sulfide solid electrolyte prepared in Example
[0102]
[0103]
[0104] Table 2 Composition and ionic conductivity of sulfide solid electrolyte prepared in comparative example
[0105]
[0106]
[0107] Table 2 Composition and ionic conductivity of sulfide solid electrolyte prepared in comparative example (continued)
[0108]
[0109] Obviously, through a large number of examples and comparative examples, it can be concluded that closed pressure sintering is beneficial to improving the ionic conductivity of sulfide solid electrolytes. At the same time, it is also found that sulfide modifiers are more advantageous than oxidizing modifiers. The reason may be attributed to the fact that the radius of sulfur is larger than that of oxygen, and the ion transport channel is larger after doping, thereby improving the ionic conductivity. It is worth mentioning that the high-density sulfide solid electrolyte Li obtained by the present invention 7 P 3-x-y-2z S 11-0.5x-0.5y- 2z Zr x Sn y In 2z It is more conducive to the transmission of lithium ions and has higher ionic conductivity. It can be clearly seen from the results in Table 1 that the ionic conductivity of the three sulfides co-doped is higher, reaching 8.82mS / cm. Among the single doping modifiers, the indium sulfide modifier is better in improving the ionic conductivity. Among them, Example 10, which is doped with indium sulfide alone, has an ionic conductivity of 2.72mS / cm; Example 1, which is doped with zirconium sulfide alone, has an ionic conductivity of 2.12mS / cm; Example 6, which is doped with tin sulfide alone, has an ionic conductivity of 1.95mS / cm; it can be seen that the ionic conductivity of multiple sulfide doping is at least 3.24 times that of single doping. Using the same method, the ionic conductivity of multiple sulfide doping can be obtained, which is at least 2.13 times that of double doping. Analyzing this reason, it may be attributed to the fact that when sulfide dopants are introduced, atoms with larger ionic radius such as Zr and Sn will replace part of [P 2 S 7 ], while In replaces the P atom on [PS 4 ] on the P atoms, thus forming an interactive chain transmission channel. Compared with the single chain transmission channel, the interactive chain transmission channel expands the [PS 4 ] structural unit. This transmission pathway not only improves the transmission rate of lithium ions in the lattice, but also changes the ion transmission pathway, thereby improving the ion conductivity. The schematic diagram of the ion transmission channel of the sulfide solid electrolyte prepared in the embodiment of the present invention is shown in FIG. Figure 2 shown.
[0110] For the sintering technology in the sulfide electrolyte synthesis process, most of them currently use powder sintering or tablet sintering. A sintering process that can be sealed and pressure-maintained adopted in the embodiment of the present invention can isolate water and oxygen in the sulfide electrolyte synthesis process, improve the crystallinity of the material, and achieve high capacity, fast charging and discharging and long cycle. Compared with the existing powder sintering (i.e. sealed crucible sintering) and tablet sintering (i.e. sealed crucible sintering after tableting), both the conductivity of the electrolyte and the electrochemical performance of the corresponding battery are significantly improved. The possible reason is that although powder sintering has the significant advantage of simple process, the material particles are exposed to the sintering atmosphere, and the volatile elements are easily lost with the atmosphere at a certain heat treatment temperature, resulting in the resulting material being easy to form a core element-deficient compound (e.g., sodium-deficient, lithium-deficient material, etc.). Similarly, tablet sintering can effectively improve the contact between particles after pressing the precursor into a sheet, but for volatile elements and sintering materials that are easy to release gas, it may easily cause pore channels on the physical scale, which in turn worsens the contact between particles.
[0111] In addition, other conditions are the same as those in Example 16. In the experiment, the pressure-maintaining sintering pressure is replaced with 96MPa, 192MPa and 288MPa, respectively, and the conductivity of the obtained sulfide solid electrolyte is measured to be 1.35mS / cm, 1.62mS / cm and 1.85mS / cm, respectively. The conductivity of the sulfide solid electrolyte obtained by pressure-maintaining sintering at 374MPa in Example 16 is 3.84mS / cm, which shows that when the sulfide solid electrolyte is prepared by pressure-maintaining sintering, the electrolyte conductivity shows an upward trend as the pressure increases.
[0112] Based on the research on improving ionic conductivity, the present invention has also conducted some research on the electrochemical properties of the prepared high-density sulfide solid electrolyte. Table 3 is a comparison of the electrochemical properties of the embodiment (sealed pressure-maintained sintering) and Table 4 is a comparison of the electrochemical properties of the comparative example (tablet-pressed sealed crucible sintering). It can be clearly seen from the electrochemical properties of the embodiments and comparative examples listed in Tables 3 and 4 that the battery assembled with the sulfide solid electrolyte after sealed pressure-maintained sintering has significant advantages in the first charge, first discharge, first efficiency and regular cycle performance. In particular, the high-density sulfide solid electrolyte Li obtained by the present invention 7 P 3-x-y-2z S 11-0.5x-0.5y- 2z Zr x Sn y In 2z The performance is particularly outstanding. The reason can also be analyzed from the fact that the doping of sulfide modifier changes the ion transmission channel and improves the transmission rate, which will not be repeated here. Specifically, the high-density sulfide solid electrolyte Li of Example 17 was prepared by closed pressure sintering. 7 P 2.6 S 10.7 Zr0.1 Sn 0.1 In 0.2 After assembling the battery, the charge and discharge rates were 0.1C, and the first cycle charge and discharge specific capacities measured at room temperature were 126.62 mAh / g and 119.89 mAh / g, respectively, with a first cycle efficiency of 94.68%, and a capacity retention rate of 91.46% after 100 cycles. However, as a comparative example 34, Example 17 was only changed to tablet sealed crucible sintering, and its electrochemical performance was far inferior to that of pressure-maintained sintering. The first cycle charge and discharge specific capacities were 124.59 mAh / g and 108.68 mAh / g, respectively, and the first cycle efficiency was 87.23%. After 100 cycles, the capacity retention rate was only 80.87%. In addition, the sample of Example 17 was also changed to sealed crucible direct sintering, and the electrochemical performance of the resulting sulfide solid electrolyte was even worse, with the first cycle charge and discharge specific capacities being 105.28 and 82.71 mAh / g, respectively, and the first cycle efficiency being 78.56%. After 100 cycles, the capacity retention rate dropped to 65.29%. In order to more intuitively compare the effects of three different sintering methods on the electrochemical properties of sulfide solid electrolytes, Figure 3 Impedance spectra of sulfide solid electrolytes prepared in some embodiments and comparative examples of the present invention. Figure 4 The following are the cycle performance curves of high entropy sulfide solid electrolytes prepared by different sintering methods. Figure 3 and Figure 4 It can also be concluded that closed high-pressure sintering is superior to the other two sintering methods.
[0113] Table 3 Electrochemical performance of assembled batteries in different embodiments at 0.1C rate
[0114]
[0115] Table 4 Electrochemical performance of batteries assembled from different comparative examples at 0.1C rate
[0116]
[0117] The above shows and describes the implementation examples of the present invention, or the technical schemes of the attached drawings, which all reflect that the preparation method of the pressure-maintained sintered sulfide solid lithium-ion battery electrolyte provided by the present invention can effectively improve the ion conductivity. It should be understood that for those skilled in the art, improvements or changes can be made according to the above description, and all these improvements and changes should belong to the protection scope of the claims attached to the present invention.
Claims
1. A high-density sulfide solid electrolyte, characterized in that: Its chemical formula is Li7P 3-x-y-2z S 11-0.5x-0.5y- 2z Zr x Sn y In 2z , where the values of x, y and z are independently 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, and x, y and z are not 0 at the same time.
2. The solid electrolyte according to claim 1, characterized in that The values of x, y and z are independently 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.2, and x, y and z are not 0 at the same time.
3. The method for preparing a solid electrolyte according to claim 1 or 2, characterized in that: The steps include: (1) weighing raw materials LiS, P2O5 and modified sulfide dopant according to the chemical formula element ratio of the solid electrolyte, and pre-mixing by ball milling to prepare an electrolyte precursor; wherein the modified sulfide dopant is a sulfide of one or more elements of Zr, Sn and In; (2) sintering the electrolyte precursor under pressure in an inert atmosphere to obtain a flaky sulfide solid electrolyte; (3) Grinding the flaky sulfide solid electrolyte to obtain a powdered sulfide solid electrolyte.
4. The preparation method according to claim 3, characterized in that: In the ball milling premixing of step (1), the mass ratio of the ball milling raw materials to the ball milling beads is 1:10 to 1:30, the ball milling speed is 200 to 600 rpm, and the ball milling time is 24 to 72 hours.
5. The preparation method according to claim 3, characterized in that: The pressure of the pressure-maintaining sintering in step (2) is maintained at 50-500 MPa, preferably 300-400 MPa.
6. The preparation method according to claim 3, characterized in that: Step (2) is specifically as follows: placing the electrolyte precursor in a pressure-maintaining sintering mold, placing the mold under a tablet press for tableting, maintaining the pressure using a pressure-stabilizing component on the sintering mold after reaching a target pressure, and then placing the pressure-maintaining sintering mold in a heating furnace, and performing pressure-maintaining sintering in an inert atmosphere to obtain the flaky sulfide solid electrolyte.
7. The preparation method according to claim 6, characterized in that: The pressure-maintaining sintering mold includes an upper mold and a lower mold. When in use, the electrolyte precursor is placed between the upper mold and the lower mold; ceramic gaskets are provided at the bottom of the upper mold and the top of the lower mold to prevent the electrolyte precursor from directly contacting the stainless steel mold; sealing ceramic rings are provided at the periphery of the upper mold and the lower mold to isolate the electrolyte precursor from the outside world; a pressure-dividing base is provided at the lower part of the lower mold; an upper top cover is provided at the top of the upper mold, and a lower bottom cover is provided at the bottom of the lower mold, and the upper top cover and the lower top cover fix the upper mold and the lower mold through a fastening device.
8. The preparation method according to claim 7, characterized in that: The fastening device comprises a fastening bolt and a fastening nut matched with the fastening bolt.
9. The preparation method according to claim 1, characterized in that: The sintering temperature of the pressure-maintaining sintering is 200-550° C., and the heating rate is 3-8° C. / min.
10. Use of the sulfide solid electrolyte according to claim 1 or 2 as a solid electrolyte for lithium ion batteries.
Citation Information
Cited By
Air-stable sulfide solid electrolyte as well as preparation method and application thereof
CN121097189A